Downlink and Uplink Cooperative Transmission for Primary Secrecy Based Cognitive Radio Sensor Networks. (27th October 2015) - Wang, Dawei; Ren, Pinyi; Du, Qinghe; Sun, Li; Wang, Yichen
Abstract : Aiming at allocating more licensed spectrum to wireless sensor nodes (SNs) under the constraint of the information security requirement of the primary system, in this paper, we propose a cooperative relaying and jamming secure transmission (CRJS) scheme in which SNs will relay primary message and jam primary eavesdrop concurrently with SN's downlink and uplink information transmission in cognitive radio sensor networks (CRSNs). In our proposed CRJS scheme, SNs take advantages of physical layer secure technologies to protect the primary transmission and acquire some interference-free licensed spectrum as a reward. In addition, both decode-and-forward (DF) and amplify-and-forward (AF) relaying protocols are investigated in our proposed CRJS scheme. Our object is to maximize the transmission rate of SNs by optimal allocating of the relaying power, jamming power, and downlink and uplink transmit power under the target secure transmission rate requirement of the primary system. Moreover, two suboptimal algorithms are proposed to deal with these optimization problems. Furthermore, we analyze the transmission rate of SNs and allocate the relaying power, jamming power, and downlink and uplink transmit power for the asymptotic scenarios. Simulation results demonstrate the performance superiority of our developed strategy over conventional jamming scheme in terms of the transmission rate of WSN.